Lung Nodule Management: An Interventional Pulmonology Perspective - Chaddha, Udit; Kurman, Jonathan S.; Mahajan, Amit; Hogarth, D. Kyle (Seminars in Respiratory and Critical Care Medicine, 2018)
With the rising number of screening and incidentally detected lung nodules, there is an increasing need for evaluation in the safest and least invasive manner. The last two decades have seen substantial evolution in bronchoscopic approaches to diagnose these nodules. Innovative bronchoscopic techniques, often used in conjunction with each other, have significantly improved our ability to navigate to almost any part of the lung. A comprehensive knowledge of available technologies and the factors affecting diagnostic yield is essential to decide on the best way to approach a particular scenario. This article provides an overview of the technical aspects, yield, and limitations of these modalities.
Keywords: lung nodule; radial endobronchial ultrasound; virtual bronchoscopy; electromagnetic navigation; robotic bronchoscopy; cone beam computed tomography